Pengaruh Implementasi Digital Marketing Terhadap Citra Merek Nike - Mohammad Adhyaksa Auliya’ul Hakim; Reza Ingatenta Sembiring; Nasrul Ikhwan; Catharina Aprilia Hellyani (Jurnal Publikasi Ilmu Manajemen, 2023)
In this increasingly modern era, many companies prioritize the company's brand image so that the company they own becomes the best company in the eyes of consumers, due to the many competitors and increasingly advanced technology, many companies are doing various ways to be able to build a brand image that can stick in their hearts. consumer. The purpose of this study was to analyze the effect of implementing digital marketing on Nike's corporate image The research method used is Descriptive Research, which is a research method aimed at describing existing phenomena that are currently taking place. Descriptive research aims to make a systematic, factual and accurate description of the facts and characteristics of a particular research object. The main purpose of implementing a digital marketing strategy is to establish communication between manufacturers and customers, and build a more specific corporate image to communicate the brand to build trust and brand loyalty among customers.